Rolled copper foil, copper-clad laminate, method for manufacturing copper-clad laminate, method for manufacturing flexible printed wiring board, and method for manufacturing electronic component

By performing 260°C heat treatment and reasonable addition of Ag alloy elements in the rolled copper foil, the Cube area ratio is improved, and the problem that the prior art cannot meet the bending requirements of electronic equipment is solved, and higher bending and stability are achieved.

CN119256110APending Publication Date: 2025-01-03JX NIPPON MINING & METALS CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380042735.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-04
Filing Date
2023-06-01
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing rolled copper foil cannot meet the increasingly stringent bending requirements under the background of thin, short and high-performance thinness, shortness and high performance of electronic devices such as smartphones.

Method used

By performing heat treatment in a 260°C dryer for 30 minutes, the Cube area ratio of the calendered copper foil is more than 94.0%, and the bending property is improved by combining appropriate Ag alloy elements and the average crystal particle size control after final annealing.

Benefits of technology

It provides higher bending properties during FPCization, stable and independent of heating conditions during the manufacture of copper clad laminated plates, ensuring excellent performance of flexible printed circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151487510000161
    Figure BDA0005151487510000161
  • Figure BDA0005151487510000181
    Figure BDA0005151487510000181
  • Figure HDA0005151487530000011
    Figure HDA0005151487530000011
Patent Text Reader

Abstract

Provided is a rolled copper foil having higher bendability than before when made into an FPC. The rolled copper foil contains 99.9% by mass or more of Cu, with the remainder comprising unavoidable impurities, and has a Cube area ratio of 94.0% or more as measured when heat-treated at an in-device temperature of 260 DEG C in a dryer for a heating holding time of 30 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a rolled copper foil, a copper-clad laminate, a method for manufacturing the copper-clad laminate, a method for manufacturing a flexible printed circuit board, and a method for manufacturing an electronic component. Background Art

[0002] Flexible printed circuits (FPCs) are made by bonding a metal conductive layer to a flexible insulating substrate such as a resin film. Copper foil is usually used as the conductive layer, and rolled copper foil with excellent flexibility is used in applications that require flexibility.

[0003] The usual FPC manufacturing steps are as follows. First, copper foil is bonded to a resin film. Regarding bonding, there is a method of coating a varnish containing a precursor of a polyimide resin on the copper foil and applying a heat treatment to imidize (casting method), and a method of overlapping and laminating a resin film having adhesiveness with the copper foil (lamination method). The copper foil with a resin film bonded by these steps is called a copper clad laminate (CCL). After that, a circuit is formed by etching to complete the FPC.

[0004] As described above, the rolled copper foil for FPC needs to be bendable. In order to provide a rolled copper foil for FPC that is easy to anneal at the curing temperature of the resin adhesive and has excellent bending resistance (bending fatigue life) after annealing, it is proposed to make the processing degree of the final cold rolling 90% or more.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent document 1: Japanese Patent Application Laid-Open No. 4-228553. Summary of the invention

[0008] Technical Problems to be Solved by the Invention

[0009] However, as electronic devices such as smartphones have become thinner, shorter, and more powerful in recent years, the bendability required of rolled copper foil has become increasingly stringent. As a result, copper foil manufactured using existing technologies is no longer able to meet customer needs.

[0010] Therefore, in one embodiment of the present invention, an object is to provide a rolled copper foil having higher bendability than ever before when converted into an FPC.

[0011] Solutions to technical problems

[0012] The present inventors have conducted various studies and have found that a rolled copper foil having high bendability can be obtained by heat treating the rolled copper foil under predetermined conditions so that the cube area ratio is 94.0% or more, and have created the invention as exemplified below. [1]

[0014] A rolled copper foil containing 99.9 mass % or more of Cu, the remainder being inevitable impurities, wherein when the rolled copper foil is heat treated at a dryer internal temperature of 260° C. and a heating holding time of 30 minutes, the cube area ratio measured is 94.0% or more. [2]

[0016] A rolled copper foil containing 99.9% by mass or more of Cu, the remainder being inevitable impurities, wherein when the rolled copper foil is heat treated at a temperature in a dryer of 260° C. and a heating holding time of 30 minutes, the arithmetic mean of the cube area ratios measured at any two points is 94.0% or more. [3]

[0018] A rolled copper foil containing 99.9% by mass or more of Cu, the remainder being inevitable impurities, wherein when the rolled copper foil is heat treated at a temperature in a dryer of 260° C. and a heating holding time of 30 minutes, the median value of the Cube area ratio obtained by measuring an arbitrary point and two points in a direction perpendicular to the rolling direction, each of which is 5 mm apart from the point, i.e., a total of three points, is 94.0% or more. [4]

[0020] A rolled copper foil containing 99.9% by mass or more of Cu, the remainder being inevitable impurities, wherein when the rolled copper foil is heat treated at a temperature in a dryer of 260° C. and a heating holding time of 30 minutes, the arithmetic mean of the cube area ratio obtained by measuring any one point and two or more points in a direction perpendicular to the rolling and equidistant from the point by 5 mm and excluding the maximum and minimum values ​​is 94.0% or more. [5]

[0022] The rolled copper foil according to any one of [1] to [4], further comprising 100 to 360 mass ppm of Ag. [6]

[0024] The rolled copper foil according to any one of [1] to [5], wherein the thickness is 4 to 35 μm. [7]

[0026] The rolled copper foil according to any one of [1] to [6], wherein the thickness is 6 to 35 μm. [8]

[0028] A copper-clad laminate having a rolled copper foil with a Cube area ratio of 94.0% or more. [9]

[0030] A method for producing a copper-clad laminate, comprising: bonding the rolled copper foil according to any one of [1] to [7] to a substrate, and performing a heat treatment in the step.

[10]

[0032] A method for manufacturing a flexible printed wiring board, comprising the steps of using the copper-clad laminate manufactured by the method for manufacturing a copper-clad laminate according to [9] as a material and forming a circuit.

[11]

[0034] A method for manufacturing an electronic component, comprising: a step of manufacturing an electronic component having a flexible printed wiring board manufactured by the method for manufacturing a flexible printed wiring board according to

[10] .

[0035] Effects of the Invention

[0036] According to one embodiment of the present invention, it is possible to provide a rolled copper foil having higher bendability than ever before when converted into an FPC. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a schematic diagram showing the measurement method of the IPC sliding bending test in Example 6 and Comparative Examples 4 and 5.

[0038] Figure 2 This is a graph plotted based on Example 6 and Comparative Examples 4 and 5, with the Cube area ratio after heat treatment at 260° C. for 30 minutes as the horizontal axis and the IPC sliding bending number as the vertical axis. DETAILED DESCRIPTION

[0039] The present invention is not limited to the embodiments described below, and the components can be modified and embodied within the scope of the gist thereof. In addition, various inventions can be formed by appropriately combining a plurality of components disclosed in the embodiments.

[0040] It should be noted that the "Cube orientation" in this specification means that the {001} plane is parallel to the rolling surface and <100> The orientation of the grains parallel to the rolling direction (RD) is represented by {001} <100> In addition, the "Cube area ratio" indicates the Cube orientation {001} <100> In addition, the "rolling direction" refers to the direction parallel to the direction in which the rolled object passes between the paired working rolls. In addition, the "rolling perpendicular direction" refers to the direction perpendicular to the rolling direction in the rolling surface.

[0041] [1. Rolled copper foil]

[0042] (Element)

[0043] In one embodiment, the rolled copper foil of the present invention contains 99.9 mass % or more of Cu, with the remainder being composed of inevitable impurities. In another embodiment, the rolled copper foil may be composed of pure Cu.

[0044] In another embodiment, the rolled copper foil may contain 100 to 360 ppm by mass of Ag as an alloy element from the viewpoint of more reliably obtaining higher bendability than before when FPC-formed and controlling at an appropriate recrystallization temperature. In particular, it is preferred that the above-mentioned additive element be contained in tough pitch copper (TPC) of JIS H 3100 (C1100) or oxygen-free copper (OFC) of JIS H 3100 (C1020).

[0045] When the Ag concentration exceeds 360 mass ppm, under the influence of the increased recrystallization temperature of the rolled copper foil, even if the heat treatment in the casting method or lamination method is implemented, the recrystallization is sometimes insufficient. If it is assumed that there are unrecrystallized grains remaining in the rolled copper foil, the bendability of the FPC will be significantly reduced. In addition, if the Ag concentration is above 100 mass ppm, the amount of rolling strain introduced will increase, so the cubic texture after the CCL heat treatment is easy to grow, and the bendability is easy to increase.

[0046] It should be noted that the upper limit of the oxygen content in the rolled copper foil is, for example, 500 mass ppm or less. In addition, the lower limit of the oxygen content in the rolled copper foil is, for example, 0 mass ppm or more. Based on the viewpoint of reducing the amount of copper oxide (CuO) in the material, the oxygen content is preferably 50 mass ppm or less, and it is generally believed that copper oxide (CuO) will have an adverse effect on the bendability of the FPC.

[0047] The composition of the rolled copper foil of the present invention can be measured by fluorescent X-ray analysis as a dry analysis. Specifically, the fluorescent X-ray analysis is measured using Simultix14 manufactured by Rigaku Corporation. The analysis surface can use a surface that has been cut or mechanically polished in a manner such that the surface maximum height roughness Rz (JIS B 0601: 2013) is 6.3 μm or less. In the case of taking a sample for analysis from the molten metal in the melt casting in the manufacturing process of the rolled copper foil, after casting into a shape of 30 to 40 mm Φ and a thickness of about 50 to 80 mm, it is cut into a thickness of about 10 to 20 mm, and the cut surface is used as the analysis surface. The analysis surface is repeatedly cut or mechanically polished until the surface maximum height roughness Rz (JIS B0601: 2013) is 6.3 μm or less.

[0048] It should be noted that, in addition to the measurement using fluorescent X-ray analysis, the composition of the rolled copper foil can also be measured using ICP emission spectrometry as a wet analysis. Specifically, it can be measured using an ICP emission spectrometry device (ICP-OES) SPS3100 manufactured by Hitachi High-Tech Sciences, Ltd. In the case of ICP emission spectrometry, the sample is dissolved in a nitric acid aqueous solution (nitric acid: water = 1:1 by volume ratio) and diluted for use.

[0049] (Cube area ratio)

[0050] In one embodiment of the rolled copper foil of the present invention, when the rolled copper foil is heat-treated at a temperature in a dryer of 260°C for a heating holding time of 30 minutes and measured using the method described below, the Cube area ratio is 94.0% or more. Specifically, a portion of the rolled copper foil is used as a sample, and the sample is placed in a dryer (manufactured by Advantech Toyo Co., Ltd.: DRH453WA) maintained at 260°C, and after heat treatment for 30 minutes in the air atmosphere, the sample is taken out of the dryer and placed in the air atmosphere for cooling. It should be noted that before the sample is placed in the dryer, in order to prevent oxidation in the air atmosphere or to prevent bending and wrinkling when taken out of the dryer, the rolled copper foil is sandwiched between two phosphor bronze (JIS H 3110 (C5210)) plates (thickness: 0.2mm) to form a laminate, and then the laminate is wrapped with a fully annealed tough copper rolled foil (thickness: 33μm) to seal it, and then placed in the dryer.

[0051] The speed at which the Cube orientation develops under the specified heat treatment conditions is relatively high, and the rolled copper foil with a Cube area ratio above the specified value is difficult to accumulate dislocations toward the crystal grain boundaries in the material when bent. As a result, the generation of cracks that cause fracture is suppressed, so the bendability is excellent, for example, stable bendability that does not depend on the heating conditions during the manufacture of the copper-clad laminate can be obtained. The lower limit of the above-mentioned Cube area ratio is preferably 95.0% or more, and more preferably 95.5% or more, more preferably 96.0% or more, more preferably 96.5% or more, and more preferably 96.6% or more, further preferably 97.0% or more, further preferably 97.5% or more, and further preferably 97.8% or more, further preferably 98.0% or more, further preferably 98.5% or more, further preferably 99.0% or more, further preferably 99.5% or more, further preferably 99.6% or more, and further preferably 99.7% or more. On the other hand, the upper limit of the above-mentioned Cube area ratio is 100.0% or less.

[0052] The inventors have found that in order to improve the Cube area ratio after heat treatment, it is important to control the average grain size after final annealing and the processing degree of final cold rolling. The various conditions of the average grain size after final annealing and the processing degree of final cold rolling will be described below.

[0053] (Measurement method of cube area ratio)

[0054] Next, an example of a method for measuring the Cube area ratio is described. The Cube orientation {001} is measured by EBSD on the surface of a rolled copper foil sample that has been heat treated at 260°C for 30 minutes as described above. <100> Here, EBSD (Electron Back Scatter Diffraction) refers to a technique for analyzing crystal orientation using Kikuchi line diffraction (Kikuchi pattern) of reflected electrons generated when an electron beam is irradiated to a sample in a SEM (Scanning Electron Microscope).

[0055] Electrolytic polishing is performed according to the following electrolyte and test conditions. After removing a thickness of about 1 μm from the sample surface, the observation range of 1000 μm × 1000 μm, which is arbitrarily set in a manner that one side of the observation field is parallel to the rolling direction, is scanned using a step size of 3 μm to measure the crystal orientation distribution. The measurement is carried out at more than two positions avoiding abnormal parts. It should be noted that if the arithmetic mean of the Cube area ratio at any two positions is 94.0% or more, the rolled copper foil as a whole tends to have higher bendability. The reason is that although there will be some deviations in the manufacturing conditions within the rolled copper foil to a certain extent in the manufacturing step, the Cube area ratio measured after the rolled copper foil obtained by the manufacturing step is subjected to heat treatment under specified conditions is roughly controlled within the required range. Therefore, when the arithmetic mean of the Cube area ratios at any two positions is greater than 94.0%, although there is a possibility that a portion of the rolled copper foil will have a Cube area ratio less than 94.0%, it can be assumed that there will not be too many such portions, and most of them will become the desired metal structure, which can solve the technical problem of the present invention.

[0056] Furthermore, due to the manufacturing and processing of rolled copper foil (for example, cutting of samples for measurement, etc.), abnormal parts such as a lot of oil pits, foreign matter attached, and rolling stripes may be generated locally. When measuring the Cube area rate, the measurement position should be set to avoid the position corresponding to the abnormal part. By using SEM (observation magnification: 100 times) to observe the sample before electrolytic polishing, etc., the abnormal part can be grasped. As mentioned above, the entire rolled copper foil should be controlled within a roughly specified range, so the measurement of the Cube area rate can be observed and measured at any two points avoiding the abnormal part, and can be observed and measured at positions with a spacing of more than 5 mm.

[0057] It should be noted that the Cube area rate can be calculated based on the arithmetic mean of n-2 points (when the measurement point is any one point and two points with an equal distance of 5 mm from the point along the vertical direction of the rolling, that is, a total of three points, it is the middle value) by measuring any one point and two or more points with an equal distance of 5 mm from the point along the vertical direction of the rolling, and removing the maximum and minimum values. When the measurement position overlaps with the abnormal part, avoid the abnormal part and measure a total of more than three points. Here, "n" refers to the total number of measurement points. The total number of measurement points can be more than 3 and less than 10, or more than 3 and less than 5. In addition, the total number of measurement points can be any one of 3, 4, 5, 6, 7, 8, 9 or 10.

[0058] <Preparation of Electrolyte Solution (One Example)>

[0059] Distilled water: 250ml

[0060] · Phosphoric acid: 125 ml

[0061] · Urea: 2.5 g

[0062] · Ethanol grade 1: 125 ml

[0063] · 1-Propanol: 25 ml

[0064] <Electropolishing conditions>

[0065] Applied voltage: 10 V

[0066] Electrolysis time: 10 s

[0067] <Measurement conditions of EBSD, etc.>

[0068] · SEM conditions

[0069] Apparatus: Scanning electron microscope (JSM-IT500HR or equivalent apparatus) manufactured by JEOL Ltd.

[0070] Type of electron gun: Field emission type electron gun (Schottky type)

[0071] Emitter of electron gun: ZrO tungsten cathode

[0072] Type of objective lens: Outer lens type

[0073] Presence or absence of focus correction: Yes (Dynamic focus: 50)

[0074] Electron beam conditions

[0075] Acceleration voltage: 15 kV

[0076] Working distance: 15 mm

[0077] Irradiation current: 15 nA

[0078] SEM probe diameter: 0.5 - 2 nm

[0079] Observation magnification: 90 times

[0080] · EBSD apparatus conditions

[0081] Detector: Slow-scan CCD camera manufactured by TSL Solutions Co., Ltd.

[0082] · Data processing conditions

[0083] Data collection software: OIM Data Collection Phase (phase) manufactured by TSL Solutions Co., Ltd.: Copper

[0084] CCD camera pixel count: 1394 × 1040 pixels

[0085] Binning (pixel combination): 8×8

[0086] Exposure: 8 milliseconds

[0087] Gain: 0.9~0.95

[0088] Background processing: Yes

[0089] Scanning method of measuring points: Hexagonal lattice

[0090] Hough transform

[0091] (1) Hough Type: Classic

[0092] (2) Hough Resolution: Low

[0093] (3) Classic Hough

[0094] Convolution Mask: 9×9

[0095] Min Peak Magnitude: 5

[0096] Min Peak Distance: 23

[0097] Peak Symmetry: 0.75

[0098] Vertical Bias: 0

[0099] (4) General Parameter

[0100] Binned Pattern Size: 120

[0101] Theta Step Size: 1°

[0102] Rho Fraction: 90%

[0103] Max Peak Count: 8

[0104] Min Peak Count: 3

[0105] Then, the analysis of the crystallographic orientation density function is carried out. The area of the grains with orientations within 15° from the Cube orientation is divided by the measured area and used as the area ratio. The above measurement data is collected using OIM Data Collection manufactured by TSL Solutions Co., Ltd., and the data analysis is performed using OIM Analysis V8 manufactured by TSL Solutions Co., Ltd. It should be noted that the information obtained from the orientation analysis of EBSD includes the orientation information of the depth of 10 nm where the electron beam enters the sample, but it is small enough compared to the measured range, so it is recorded as the area ratio.

[0106] <Data analysis conditions for OIM Analysis V8>

[0107] · New Map (new figure) window

[0108] Map type (figure type)

[0109] Grayscale (gray scale): Select <None>.

[0110] Color Coded (color coding): Select Crystal Orientation (crystal orientation).

[0111] Boundaries (grain boundaries)

[0112] Second Partition (second partition): Select <None>.

[0113] · Crystal Orientation (crystal orientation) window (the screen displayed when clicking Edit of Color Coded in the Map Style window)

[0114] · Display method (Representation): Select Euler Angles (Euler angles) (Bunge).

[0115] · Check box for Enforce Orthotropic Sample Symmetry (enhance orthotropic sample symmetry): Checked.

[0116] · Add Crystal Orientation Range (increase crystal orientation range) window (the screen displayed when clicking Add in the CrystalOrientation (crystal orientation) window)

[0117] Orientation (orientation) label

[0118] Phase: Select Copper.

[0119] Euler Angles (Bunge): (φ1, φ, φ2) = (0, 0, 0)

[0120] hkl input values: 001

[0121] Each input value of uvw: 100

[0122] Tolerance Tab

[0123] Minimum input value: 0

[0124] Maximum input value: 15

[0125] The value of Total fraction in the measurement result of Crystal Orientation performed under the above-mentioned setting conditions was used as the Cube area ratio.

[0126] (Average grain size after final annealing)

[0127] In one embodiment of the rolled copper foil of the present invention, it is preferred that the average grain size before the final cold rolling and after the recrystallization annealing 3 (final annealing) in the manufacturing example described below is greater than 15 μm and less than 35 μm. Generally, the smaller the grain size, the easier it is to accumulate the dislocation strain that becomes the driving force of the primary recrystallization during the final cold rolling. Therefore, by making the average grain size before the final cold rolling and after the final annealing greater than 15 μm and less than 35 μm, the cubic texture is very developed during the heat treatment of the rolled copper foil, and the bendability is improved. On the other hand, when the average grain size after the final annealing is more than 35 μm, the dislocation strain is not easy to accumulate during the final rolling, and the shear band in the rolled structure is easy to become developed. The shear band is easy to become the generation site of the non-Cube-oriented nucleus during the heat treatment of the rolled copper foil, so the cubic texture is difficult to become developed.

[0128] (Method for measuring average crystal grain size)

[0129] Next, an example of a method for measuring the average crystal grain size is described. The average crystal grain size is measured by EBSD on the sample surface after the final annealing.

[0130] Electropolishing was performed under the above conditions. After removing a thickness of about 1 μm from the sample surface, the observation range of 1000 μm × 1000 μm was arbitrarily set and scanned with a step size of 3 μm. After that, the average grain size when the boundary with a crystal orientation difference greater than 5° was regarded as a crystal grain boundary was measured by the Area Fraction method. The above analysis was performed using OIM Analysis V8 manufactured by TSL Solutions Co., Ltd. The measurement conditions of EBSD not shown below are as described above.

[0131] <Detailed settings of OIM Analysis V8 when calculating the average grain size>

[0132] ·Detailed settings of the Partition Properties window

[0133] Grain Size Tab

[0134] Input value for Grain Tolerance Angle: 5

[0135] Minimum Size [points]

[0136] Grains input value: 2

[0137] Anti-grains input value: 2

[0138] Input value for Minimum Confidence Index (minimum CI value): 0

[0139] Check the box for Apply partition before calculation: Check it.

[0140] Include grains at edges of scan in statistics checkbox: Check.

[0141] Twin Boundaries window (screen displayed when you click Define in Partition Properties)

[0142] Enforce matching between twin planes(K1)in grain A and grain B check box: Check.

[0143] Allowed tolerance between twin planes (K1s) [degrees]: 1

[0144] (Twins that are excluded are not specifically specified. Crystal grain boundaries include twins.)

[0145] Detailed settings of the New Chart window for calculating the average grain size

[0146] Type: Grain Size (diameter)

[0147] In the measurement results of Grain Size carried out under the above-mentioned setting conditions, the value of Area within Average (average value according to the Area Fraction method) is used as the average crystal grain size.

[0148] (thickness)

[0149] In one embodiment, the thickness of the rolled copper foil is, for example, 4 to 35 μm, and for example, 6 to 35 μm. The upper limit of the thickness of the rolled copper foil is, for example, 35 μm or less, and for example, 18 μm or less, and the lower limit is, for example, 4 μm or more, and for example, 6 μm or more, and for example, 9 μm or more.

[0150] It should be noted that the thickness of the rolled copper foil is measured as follows: for example, an X-ray generator is set on the surface side of the rolled copper foil, and an X-ray detector is set on the front side of the other side. The attenuation caused by the rolled copper foil is calculated based on the measured amount of penetrating X-rays, and the attenuation is converted into the thickness of the rolled copper foil. For example, the weight of a 20 cm square rolled copper foil is measured, and the value is calculated by (weight (g) / (density of rolled copper foil (g / cm 3 )×Area of ​​rolled copper foil (cm 2 )) Calculate the thickness of the rolled copper foil (It should be noted that the density of the rolled copper foil is 8.94 g / cm for oxygen-free copper according to JIS H 3100 (C1020), for example. 3 For another example, a digital measuring machine (for example, Micro Digital MH-15M manufactured by Nikon Corporation) is used to measure at two or more arbitrary points, and the thickness of the rolled copper foil is calculated from the arithmetic mean of the thicknesses.

[0151] (Manufacturing Example of Rolled Copper Foil)

[0152] As an example of a method for manufacturing a rolled copper foil, first, a melting furnace is used to melt raw materials such as copper to obtain a molten metal of the desired composition. Then, an ingot is manufactured by flowing the molten metal into a mold (casting). In order to prevent oxidation loss of copper, melting and casting are preferably carried out in a vacuum or in an inert gas atmosphere. Afterwards, the following steps are implemented in sequence: homogenization annealing, hot rolling, cold rolling 1, recrystallization annealing 1, surface cutting, cold rolling 2, recrystallization annealing 2, pickling-grinding, cold rolling 3, recrystallization annealing 3 (final annealing), and final cold rolling to form a rolled copper foil having the desired thickness and desired properties. That is, in the present invention, the rolled copper foil can be said to basically refer to the copper foil after the final cold rolling.

[0153] It should be noted that according to the empirical speculation of the present inventors, the Cube area ratio of the rolled copper foil after heat treatment at 260°C for 30 minutes is greatly affected by the average grain size after the final annealing and the degree of processing in the final cold rolling when the rolled copper foil is manufactured according to the steps described below.

[0154] (Final Annealing)

[0155] In order to improve the Cube area rate when the heat treatment is performed at 260°C for 30 minutes, the conditions of the final annealing are appropriately set. Specifically, the conditions of the final annealing can be appropriately set so that the average grain size after the final annealing is greater than 15 μm and less than 35 μm. The conditions can be changed according to the composition of the copper material. Based on the annealing conditions disclosed in this embodiment and the comparative example, those skilled in the art can experimentally determine the annealing conditions without too much trial and error.

[0156] (Final cold rolling)

[0157] The rolled copper foil can be obtained by performing the final cold rolling under the condition that the processing degree is greater than 98% and less than 99%. At this time, the thickness of the rolled copper foil is about 4 to 35 μm. It should be noted that the processing degree is defined as processing degree (%) = {(thickness before final cold rolling (mm) - thickness after final cold rolling (mm)) / thickness before final cold rolling (mm)} × 100.

[0158] [2. Method for manufacturing copper-clad laminate]

[0159] In one embodiment of the method for manufacturing a copper-clad laminate of the present invention, the step of bonding the rolled copper foil as described above to a substrate is included. As such a substrate, for example, a resin film can be cited. In order to bond the resin film to the rolled copper foil, several methods can be used.

[0160] For example, the following method can be used: using an adhesive formed of a thermosetting resin such as an epoxy resin, the rolled copper foil and the polyimide resin film are bonded together and heat-treated. Alternatively, the following method can be used: a varnish containing polyamic acid as a precursor of the polyimide resin is applied to the surface of at least one side of the rolled copper foil and heated and cured to form a polyimide coating on the surface of at least one side of the rolled copper foil.

[0161] In addition, in the case of double-sided laminated rolled copper foil, there are a method of forming a single-sided copper-clad laminate and then pressing the rolled copper foil layer by hot pressing, and a method of sandwiching a polyimide resin film between two rolled copper foil layers and pressing them by hot pressing. These heat treatments are usually carried out under the conditions of 125 to 360° C. and 30 to 400 minutes.

[0162] Furthermore, there is also a method of laminating the rolled copper foil and the resin film by using an adhesive without the heat treatment step. As the material of the resin film, polyester, polyimide, polyethylene terephthalate, polyethylene naphthalate, etc. can be listed, but it is not limited to these.

[0163] In addition, before laminating the rolled copper foil and the resin film, the rolled copper foil may be subjected to a roughening treatment, thereby increasing the bonding strength between the resin film and the rolled copper foil. For example, the roughening treatment may be performed under the following conditions.

[0164] <Roughening Treatment Conditions>

[0165] Liquid composition: Cu: 10-20 g / L, Co: 1-10 g / L, Ni: 1-15 g / L

[0166] pH: 1-4

[0167] Temperature: 30~50℃

[0168] Current density (Dk): 20~50A / dm 2

[0169] Time: 1 to 5 seconds

[0170] According to this manufacturing method, since the heat treatment develops Cube orientation, a copper-clad laminate having a copper foil (rolled copper foil) and a substrate (resin film) with a Cube area ratio of 94.0% or more can be manufactured. The method for measuring the Cube area ratio is the same as the method described above.

[0171] [3. Method for manufacturing flexible printed wiring board]

[0172] In one embodiment, the method for manufacturing a flexible printed circuit board of the present invention includes using a copper-clad laminate manufactured by the method for manufacturing a copper-clad laminate as described above as a material and forming a circuit. At this time, the copper-clad laminate can be used as a material and a circuit can be formed according to known steps to manufacture a flexible printed circuit board (FPC). For example, the following method can be cited: the copper-clad laminate is coated with a resist only on the necessary part as a conductor pattern on the rolled copper foil surface of the copper-clad laminate, and then an etching solution is sprayed on the rolled copper foil surface to remove the unnecessary rolled copper foil to form a conductor pattern, and then the resist is peeled off or removed to expose the conductor pattern. After the conductor pattern is formed, a protective covering film is usually attached.

[0173] (use)

[0174] Such FPC is used in the movable part in the hard disk, the hinge part and the sliding part of the mobile phone, the inside of the mobile phone, the head of the printer, the optical pickup part, the movable part of the portable PC, etc. in the electronic parts of the electronic equipment or the electric equipment. It should be noted that the manufacturing method of the electronic component may include the step of manufacturing an electronic component having a flexible printed circuit board manufactured by the manufacturing method of the above-mentioned flexible printed circuit board.

[0175] <Example>

[0176] The present invention will be specifically described based on Examples and Comparative Examples. The following Examples and Comparative Examples are merely specific examples given to facilitate understanding of the technical content of the present invention, and the technical scope of the present invention is not limited to these specific examples.

[0177] It should be noted that "OFC" in Tables 1 and 2 refers to oxygen-free copper in accordance with JIS H 3100 (C1020) and "TPC" refers to tough pitch copper in accordance with JIS H 3100 (C1100).

[0178] [Examples 1 to 5 and Comparative Examples 1 to 3]

[0179] [Manufacture of rolled copper foil]

[0180] First, in Examples 1 to 5 and Comparative Examples 1 to 3, an ingot is melt-cast, and the ingot has the alloy composition shown in Table 1 obtained by adding a specified metal to oxygen-free copper. It should be noted that the Ag content of the ingot is measured by the ICP emission spectrometry method described above. The ingot is processed in the following order to produce a rolled copper foil. It should be noted that the degree of processing in Table 1 is the thickness reduction rate in the final cold rolling, which is calculated by the following formula: degree of processing (%) = {(thickness before final cold rolling (mm) - thickness after final cold rolling (final product) (mm)) / thickness before final cold rolling (mm)} × 100.

[0181] <Steps (1) to (11)>

[0182] (Step 1) Homogenization annealing: The above ingot was heated at 920° C. and maintained for 2.5 hours.

[0183] (Step 2) Hot rolling: The ingot heated at 920° C. was rolled at room temperature to a thickness of 16 mm, and then rapidly cooled to room temperature by water cooling to obtain a strip-shaped metal material.

[0184] (Step 3) Cold rolling 1: rolling to a thickness of 10.5 mm.

[0185] (Step 4) Recrystallization annealing 1: The strip-shaped metal material is heated at 400° C. and maintained for 7.5 hours.

[0186] (Step 5) Surface cutting: The oxide layer on the surface is removed by surface cutting.

[0187] (Step 6) Cold rolling 2: rolling to a thickness of 1.5 mm.

[0188] (Step 7) Recrystallization annealing 2: Maintain in a furnace heated to 750°C for 30 to 120 seconds.

[0189] (Step 8) Pickling and polishing: After immersion in a mixed acid of sulfuric acid and hydrogen peroxide, the oxide film on the surface of the material is removed by polishing.

[0190] (Step 9) Cold rolling 3: rolling to a thickness of 0.8 mm.

[0191] (Step 10) Recrystallization annealing 3 (final annealing): The annealing temperature and holding time are adjusted to obtain a specified grain size, and the strip metal material after cold rolling 3 is heated and kept warm respectively. Table 1 records the annealing conditions of each sample. It should be noted that in order to prevent oxidation, the above-mentioned strip metal material is wrapped and sealed with a rolled copper foil (thickness: 33μm) of fully annealed tough copper (JIS H 3100 (C1100)) to obtain a sealed body placed in a dryer. After heating and keeping warm, the sealed body is taken out of the dryer and placed in an atmospheric atmosphere for cooling. After being placed and cooled, the strip metal material is taken out from the sealed body. Then, the average grain size after the final annealing is determined by the above-mentioned method.

[0192] (Step 11) Final cold rolling: Finishing to a thickness of 0.012 mm (12 μm) to obtain rolled copper foil. In the final cold rolling, the two ends of the strip metal material in the rolling direction are not fixed (free end state), and the strip metal material is passed between the paired working rolls and rolled in a manner that does not act in a direction parallel to the rolling direction.

[0193] It should be noted that in Examples 1 to 5 and Comparative Examples 1 to 3, recrystallization annealing 3 was carried out at the annealing temperatures and holding times described in Table 1.

[0194] [Characteristic evaluation]

[0195] <Evaluation of Cube area ratio>

[0196] Next, in Examples 1 to 5 and Comparative Examples 1 to 3, a part of the rolled copper foil obtained by the above manufacturing was taken as each measurement sample. By the method described above, a laminate was obtained by sandwiching the measurement sample with two phosphor bronze (JIS H 3110 (C5210) standard) plates (thickness: 0.2 mm). Then, the laminate was wrapped and sealed with a rolled copper foil (thickness: 33 μm) of fully annealed tough copper (JIS H 3100 (C1100)) to obtain a sealed body. The sealed body was placed in a dryer and heat-treated at an internal temperature of 260 °C in the dryer and a heating holding time of 30 minutes. After the heat treatment, it was taken out of the dryer and allowed to cool in the atmospheric atmosphere. After allowing to cool, the rolled copper foil used as the measurement sample was taken out from the sealed body. The sample surface of the rolled copper foil after the heat treatment was regarded as the measurement object, and the area ratio of the Cube orientation {001}<100> of the rolled copper foil after the heat treatment was measured by the method described above using a scanning electron microscope (JSM-IT500HR) manufactured by JEOL Ltd. It should be noted that in Tables 1 and 2, the arithmetic average of the area ratios of the Cube orientation {001}<100> at two points measured avoiding abnormal parts was shown as the Cube area ratio. It should be noted that an attempt was made to measure the Cube area ratio in the same way for the rolled copper foil after the final cold rolling and before the heat treatment at 260 °C for 30 minutes. However, since the sizes of the sub-grain and dislocation cell structures in the rolling texture were smaller than the step size (3 μm) of the EBSD measurement conditions, it was impossible to measure under the same conditions as those for the samples of the rolled copper foil after the heat treatment.

[0197]

[0198]

[0199] (Investigation 1 of the example)

[0200] Examples 1 to 5 were compared with Comparative Examples 1 to 3, and it was found that on the basis that the degree of cold rolling in the final cold rolling was greater than 98% and less than 99%, by appropriately setting the average crystal grain size after the final annealing, the Cube area ratio of the rolled copper foil after heat treatment at 260 °C for 30 minutes could be increased. In addition, Example 3 was compared with Example 4, and it was confirmed that the smaller the average crystal grain size after the final annealing, the higher the tendency of the Cube area ratio of the rolled copper foil during heat treatment at 260 °C for 30 minutes.

[0201] [Example 6 and Comparative Examples 4 to 5]

[0202] In Example 6 and Comparative Examples 4 to 5, in order to confirm the relationship between the Cube area ratio and the bendability, rolled copper foils having the Cube area ratio described in Table 2 were prepared respectively when heat treated at 260 °C for 30 minutes. It should be noted that, similar to the evaluation of the above Cube area ratio, the arithmetic mean of the area ratios of the Cube orientations {001}<100> at two points measured avoiding abnormal parts was taken as the Cube area ratio. In addition, for the rolled copper foil after the final cold rolling and before heat treatment at 260 °C for 30 minutes, although an attempt was made to measure the Cube area ratio, similar to Example 1, it was impossible to measure it under the same conditions as the measurement conditions of the sample of the rolled copper foil after heat treatment.

[0203] <IPC Sliding Bend Test>

[0204] In Example 6 and Comparative Examples 4 to 5, a part of the rolled copper foil after the final cold rolling, that is, before heat treatment at 260 °C for 30 minutes, was taken as each measurement sample. On one surface of the measurement sample, after roughening plating treatment with reference to the above roughening plating treatment conditions, Pixio (trademark) FRS grade (thickness 25 μm) manufactured by Kaneka Corporation, which is a polyimide resin film, was laminated on the roughening plating treatment surface side of the rolled copper foil, and was pressed by hot pressing treatment at 360 °C for 30 minutes to produce a single-sided copper-clad laminate composed of two layers of a rolled copper foil and a polyimide resin film. Then, using a known photolithography technique, a circuit was formed in such a manner that the circuit width (Line) of the rolled copper foil and the interval (Space) between adjacent circuits were Line / Space = 300 μm / 300 μm, thereby producing an FPC. Next, a test piece was cut out from the obtained FPC in such a manner that the width was 12.7 mm, the length was 130 mm, and the length direction of the test piece was parallel to the rolling direction. By Figure 1The IPC (Association of Printed Circuit Industries) bending test device 100 shown in the figure is used to measure the number of IPC sliding bendings on the test piece. The IPC bending test device 100 is a structure in which a vibration transmission component 20 is combined with a vibration driving body 10, and the test piece 30 is fixed to the device at a total of four points, namely, the part of the screw 40 indicated by the arrow and the top end of the vibration transmission component 20. When the vibration transmission component 20 is driven up and down, the middle part of the test piece 30 is bent into an arc shape with a specified curvature radius r. The IPC sliding bending test is carried out under the conditions of a curvature radius r of 2.5 mm (outer radius), a vibration stroke of 20 mm, and a vibration speed of 1500 times / minute.

[0205] It should be noted that in the IPC sliding bending test, the number of times until the bending is repeated under the above conditions until the fracture is counted, and the number of test implementations under each condition is set to 4 times to implement the IPC sliding bending test. The average value of the number of times until the fracture is obtained is used as the IPC sliding bending number and is shown in Table 2. It should be noted that the fracture mentioned here means that the electrical impedance of the FPC before the IPC sliding bending test has increased by 20%. The electrical impedance is measured by the 4-terminal method.

[0206]

[0207]

[0208] (Examination of Example 2)

[0209] Based on the comparison of the results obtained in Example 6 with the results obtained in Comparative Examples 4 to 5, it can be confirmed that when an FPC is made using a rolled copper foil with a high cube area ratio measured after heat treatment at a temperature inside a dryer of 260°C for a heating holding time of 30 minutes, it has better bendability than before.

[0210] It should be noted that the horizontal axis is the cube area ratio of each sample in Table 2 after heat treatment at 260°C for 30 minutes, and the vertical axis is the IPC sliding bending number. Figure 2 In addition, the approximate straight line is calculated by the approximate curve straight line approximation function of Microsoft (registered trademark) Excel. Figure 2 The approximate formula of the straight line is shown together with the square of R. The closer the square of R is to 1, the more appropriately the approximate straight line shows the trend of the experimental data. It can be seen that there is a positively proportional correlation between the Cube area ratio and the IPC sliding bending number after heat treatment at 260°C for 30 minutes.

[0211] based on Figure 2The approximate straight line of the invention shows that when the number of IPC sliding bending times increases by more than 15% compared with the comparative example 4 as the existing product, that is, the Cube area ratio after the heat treatment at 260°C for 30 minutes with the number of IPC sliding bending times of more than 220,000 times is reversely converted, it is 93.5%. It can be inferred that by using a rolled copper foil with a Cube area ratio of more than 94.0% after the heat treatment at 260°C for 30 minutes, a rolled copper foil having higher bendability than before can be provided when FPC is applied. In addition, when the number of IPC sliding bending times increases by more than 20% compared with the comparative example 4 as the previous product (that is, the number of IPC sliding bending times is more than 230,000 times), the Cube area ratio after the heat treatment at 260°C for 30 minutes is reversely converted, it is 94.9%. It can be inferred that by using a rolled copper foil with a Cube area ratio of more than 95.0% after the heat treatment at 260°C for 30 minutes, a rolled copper foil having higher bendability than before can be provided when FPC is applied.

[0212] Explanation of symbols

[0213] 10: Vibration drive body

[0214] 20: Vibration transmission components

[0215] 30: Test piece

[0216] 40: Screw

[0217] 100:IPC bending test device

[0218] r: radius of curvature.

Claims

1. A rolled copper foil containing 99.9 mass % or more of Cu, the remainder being composed of inevitable impurities, wherein when the rolled copper foil is heat-treated at a temperature in a dryer of 260° C. and a heating holding time of 30 minutes, the cube area ratio measured is 94.0% or more.

2. A rolled copper foil containing 99.9% by mass or more of Cu, the remainder being composed of inevitable impurities, wherein when the rolled copper foil is heat treated at a dryer internal temperature of 260° C. and a heating holding time of 30 minutes, the arithmetic mean of the cube area ratios measured at any two points is 94.0% or more.

3. A rolled copper foil containing 99.9% by mass or more of Cu, the remainder being inevitable impurities, wherein when the rolled copper foil is heat treated at a temperature in a dryer of 260° C. and a heating holding time of 30 minutes, the median value of the Cube area ratio obtained by measuring any one point and two points in a direction perpendicular to the rolling direction, each of which is 5 mm apart from the point, i.e., a total of three points, is 94.0% or more.

4. A rolled copper foil containing 99.9% by mass or more of Cu, the remainder being inevitable impurities, wherein when the rolled copper foil is heat treated at a temperature in a dryer of 260° C. and a heating holding time of 30 minutes, the arithmetic mean of the cube area ratio obtained by measuring any one point and two or more points in a direction perpendicular to the rolling and equidistant from the point by 5 mm and excluding the maximum and minimum values ​​is 94.0% or more. 5 . The rolled copper foil according to claim 1 , further comprising 100 to 360 mass ppm of Ag. 6 . The rolled copper foil according to claim 1 , which has a thickness of 4 to 35 μm. 7 . The rolled copper foil according to claim 1 , which has a thickness of 6 to 35 μm.

8. A copper-clad laminate comprising a rolled copper foil having a Cube area ratio of 94.0% or more.

9. A method for manufacturing a copper-clad laminate, comprising: A step of bonding the rolled copper foil according to any one of claims 1 to 7 to a substrate, and performing a heat treatment in the step.

10. A method for manufacturing a flexible printed circuit board, comprising: A step of using the copper-clad laminate produced by the method for producing a copper-clad laminate according to claim 9 as a material and forming a circuit.

11. A method for manufacturing an electronic component, comprising: A step of manufacturing an electronic component having a flexible printed wiring board manufactured by the method for manufacturing a flexible printed wiring board according to claim 10.

Citation Information

Patent Citations

  • Bending resisting rolled copper foil

    JP1992228553A